The role of the Jakarta reading movement in fostering children's reading interest in DKI Jakarta Province - Adilla Federica Sasfitri (Universitas Wiralodra, 2023)
This research was written in a framework to see and describe new ways of fostering interest in reading through the Jakarta Reading Movement in the form of reading challenges given to children. The purpose of the study was to find out how the establishment process and innovations carried out by the Jakarta Reading Movement through the Jakarta Library and Archives Service (Dispusip) DKI Jakarta and see the various elements in it through social media activities, professionals, volunteers, utilization, and collaborative efforts with stakeholders in multiple sectors. This research uses a literature study, literature review, and digital observation with secondary data sources. The collection technique utilizes various information recorded on the official Baca Jakarta social media accounts, Instagram @bacajakarta, reference books, and scientific journals. Data processing and analysis use Miles and Huberman, a data analysis model consisting of four stages: data collection, data reduction, data presentation, and conclusion drawing. The results showed that the Jakarta Reading Movement is an initiative of the DKI Jakarta Government, through the DKI Jakarta Dispusip provides a new way for the community to foster a positively received interest in reading; various supports are received through collaboration with literacy activists, reading societies, and Regional Owned Enterprises (BUMD). The existence of the Jakarta Reading Movement has proven successful in fostering interest in reading, as seen from the participants’ enthusiasm, which increases yearly.